1968
DOI: 10.1002/pol.1968.160060509
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding in butadiene copolymers. I. Network formation

Abstract: SynopsisThe incorporation of comonomers bearing functional groups yields butadiene copolymers capable of hydrogen bonding. Three such butadiene-based materials were studied: methacrylic acid copolymers, 2-methyl-5-vinylpyridine copolymers, and stoichiometric mixtures of the acidic and basic copolymers. The elastic effects of intermolecular hydrogen bonding were determined by comparing the simple weighted average of the moduli of the parent copolymers with the observed modulus of their stoichiometric mixture. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The degree to which hydrogen bonding affects the final material properties in these and other polymeric systems remains a source of much controversy. Some studies [20,21] have predicted and shown that break up of hydrogen bonding can be a source of mechanical loss while others [22,23,24] have noted only minimal changes between systems with and without hydrogen bonding. The usual segmented urethane systems do have considerable hydrogen bonding capabilities for both intra-and inter-segment interaction and many observed characteristics have been ascribed to them [12,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which hydrogen bonding affects the final material properties in these and other polymeric systems remains a source of much controversy. Some studies [20,21] have predicted and shown that break up of hydrogen bonding can be a source of mechanical loss while others [22,23,24] have noted only minimal changes between systems with and without hydrogen bonding. The usual segmented urethane systems do have considerable hydrogen bonding capabilities for both intra-and inter-segment interaction and many observed characteristics have been ascribed to them [12,25,26,27].…”
Section: Introductionmentioning
confidence: 99%